1994
DOI: 10.1103/physrevd.49.1740
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear neutrino oscillations in the expanding Universe

Abstract: We derive the equations that govern neutrino and antineutrino behavior in the early Universe. Results are presented from numerical simulations incorporating nonlinear effects of the neutrinoantineutrino background as well as the leading CP-symmetric and CP-asymmetric terms arising from the interactions with electrons and positrons. A broad spectrum of neutrino and antineutrino behavior is observed, ranging from vacuumlike to smooth. Oscillations exhibiting self-maintained coherence also appear. We identify a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
98
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(100 citation statements)
references
References 23 publications
1
98
1
Order By: Relevance
“…(58) is traced back to the negative sign in the term (1 − v q · v p ) in Eq. (5). Therefore, the instability of the near-isotropic neutrino gas, for the normal hierarchy, is not just caused by different angular modes experiencing different neutrino-neutrino effects.…”
Section: Normal Hierarchymentioning
confidence: 99%
See 1 more Smart Citation
“…(58) is traced back to the negative sign in the term (1 − v q · v p ) in Eq. (5). Therefore, the instability of the near-isotropic neutrino gas, for the normal hierarchy, is not just caused by different angular modes experiencing different neutrino-neutrino effects.…”
Section: Normal Hierarchymentioning
confidence: 99%
“…Therefore, if the energy spectrum is broad, the energy dependence of the oscillation frequency quickly leads to kinematical decoherence, i.e., along a neutrino beam the overall flavor content quickly approaches an average value. The situation changes radically when neutrinos themselves provide a significant refractive effect, leading to collective oscillation modes [1,2,3,4,5,6,7,8,9,10,11,12] that can be of practical interest in the early universe [13,14,15,16] or in core-collapse supernovae [17,18,19,20,21,22,23,24,25,26]. Defining the parameter…”
Section: Introductionmentioning
confidence: 99%
“…Because of the neutrino-neutrino forward scattering potential [4][5][6], neutrino flavor transformation in the early universe and near the supernova core can be very different from that in the vacuum or in an ordinary matter background only [7][8][9][10][11][12][13][14][15][16][17]. Recent analytical and numerical studies have revealed a new paradigm for neutrino flavor transformation in supernovae [18][19][20][21][22][23][24][25][26], one which is completely different from vacuum oscillations or the conventional Mikheyev-Smirnov-Wolfenstein (MSW) mechanism [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The gauge boson diagrams that contribute to the one loop neutrino self-energy are the W -lepton diagram, Σ (1) , and the Z-neutrino diagram, Σ (2) , and they are given by…”
Section: Computation Of the Self-energymentioning
confidence: 99%
“…In other words, the degeneracy among the massless neutrinos is removed through the interactions with the charged leptons. This can be of immediate interest since even a slight generational asymmetry among the neutrinos can lead to resonant neutrino oscillations [2] and change the evolution of the early universe.…”
Section: Introductionmentioning
confidence: 99%